Implementasi Pemberdayaan Masyarakat Melalui Rumah Belajar Hidroponik Yang Bernilai Ekonomis Di Rptra Kamal Bahari - Muhiroh (Gunung Djati Conference Series, 2022)
Kamal is the urban village located in kalideres Sub-district west Jakarta, the area of the capital Jakarta, Indonesia. The emergence of social institutions is also a need to adapt to social changes and produce an informed and rrational form of relationships. So it was founded RPTRA (Ruang Publik Terpadu Ramah Anak) Kamal Bahari as social institutions that have an important role as centers for public empowerment. RPTRA (Ruang Publik Terpadu Ramah Anak) Kamal Bahari its is one of the most supported policies of governments province special capital district of Jakarta. In order to get the necessities of life met especially in childern of an early age. The empowering public activities that empower society are also found in the work programs or activity designs of social institutions RPTRA Kamal Baharione of the activities that researchers have observed is about Rumah Belajar Hidroponik RPTRA Kamal Bahari. The purpose of this study is to know the implemetation of society’s empowerment through hydroponics learning homes that are economically valuable RPTRA Kamal Bahari. The study employs a qualitative approach with a descriptive type of research. Whereas in the taking of informants at random using in-depth interview techniques and direct observation.